Exposure Response Supports Therapeutic Drug Monitoring for Dabigatran Etexilate in Patients with Atrial Fibrillation - Simpson, Bryan H.; Reith, David M.; Medlicott, Natalie J.; Smith, Alesha J. (TH Open, 2019)
Background Dabigatran etexilate has become widely used for the prevention of stroke in patients with nonvalvular atrial fibrillation (NVAF). Currently, there is limited information in real-world patients relating to dabigatran etexilate exposure and response.Methods This retrospective cohort study used administrative health data for NVAF patients dispensed dabigatran etexilate between July 1, 2011 and December 31, 2015. Outcomes of cerebrovascular accident (CVA), systemic embolism, and hemorrhage were extracted. Simulated pharmacokinetic parameters were obtained using a published population pharmacokinetic model of dabigatran etexilate. Area under the curve calculated for a 24-hour period at steady state (AUCss), the exposure parameter, was derived using these simulations and the dosing data and the exposure–response relationship were investigated. The risk of adverse outcomes at AUCss quartiles was compared using Poisson regression and expressed using incidence rate ratios (95% confidence interval) adjusted for known potential confounders.Results In total, 2,660 NVAF patients had been dispensed dabigatran etexilate. For these patients there was a decreased risk of hemorrhage (0.51, 0.32–0.79) when dabigatran AUCss was in the second quartile range of 1.70 to 1.96 mg h/L and thromboembolism/CVA (0.34, 0.16–0.76) when in the third quartile range of 1.97 to 2.26 mg h/L. An increased risk of hemorrhage (1.68, 1.18–2.38) was observed when AUCss was in the fourth quartile range of 2.27 to 12.76 mg h/L.Conclusion An exposure–response relationship for dabigatran etexilate was described, where the most effective response was observed when AUCss was in the range of 1.70 to 2.26 mg h/L. Hence, it is feasible to develop guidance for optimal dosing to improve outcomes for patients with NVAF.
Keywords: dabigatran etexilate; therapeutic drug monitoring; hemorrhage; stroke; population pharmacokinetic